Thermal energy storage enhancement using 3D printed structures in phase change materials - Lee, Daryl Ruo Cong (Nanyang Technological University, 2023)
This project aims to analyse and compare the thermal performance of a topologically optimised heat sink, as compared to a conventional pin fin and plate fin heat sink for thermal energy storage applications. All three fins were designed with the same material to maintain identical thermophysical properties and the same overall surface area, volume, and base plate size. A special metal additive manufacturing method known as SLM is used to 3D print all three heat sinks. A particular experimental setup was prepared to adapt and fit to the boundary limitations of the optimised heat sink. The performance of the heat sinks was analysed and assessed by melting a certain PCM, specifically “RT35” from RUBITHERM. A constant volume of PCM was used in the experimental setup each time so that a theoretical PCM vertical height of 5 cm could be achieved once the PCM had solidified. The heat sinks were experimented by the same heating conditions, via the constant base plate temperature but at three different temperatures (75˚C, 70˚C, 65˚C). A constant source of flowing hot water from a heated water bath passes through the hot plate to maintain the constant plate temperature condition for the various tests. Three different experiments, Melting Visualisation, Melt Fraction, and Melt Performance experiments were conducted to evaluate the melting characteristics and heat sinks performance. The graphic illustrations, experimental and numerical data serve as evidence to validate the individual performance of each separate heat sink. The obtained experimental results show that the TO fin has exceptionally better melting performance, disseminates heat more evenly across the device and melts the PCM faster, all the while keeping a more consistent base plate temperature throughout the experiment. The TO fin improved melt time by around 15 min when melting RT35 under the constant base plate temperature condition at lower temperatures of 70˚C and 65˚C as compared to the Plate and Pin fin. However, the results are very similar in performance when it comes to a higher temperature of 75˚C where all three heat sinks completed the experiments with very close timings.